Restoring the American Chestnut: Optimizing Founder Spacing to Promote Population Growth and Genetic Diversity Retention. Issue 5 (14th July 2014) - Rogstad, Steven H.; Pelikan, Stephan
Abstract Efforts are underway to return the American chestnut (Castanea dentata) to eastern forests of North America following its decline due to the introduction of the chestnut blight (Cryphonectria parasitica). Approaches include developing blight‐resistant chestnut lines through breeding programs and via genetic engineering. Reestablishment of resistant chestnut to eastern forests would produce one of the most extensive ecological restoration transformations ever attempted. However, this undertaking is costly and optimization of reintroduction methods is needed. We used the computer program NEWGARDEN to model whether some patterns of founder placement (regular vs. random spacing at differing densities) produce more rapidly expanding populations across a range of gene dispersal distance conditions (via both offspring and pollen). For a simulated introduction project employing 169 founders, placing founders randomly in a square of side 0.85 km produced higher rates of predicted population growth compared with larger or smaller squares under near gene dispersal conditions; this side distance was 1.0 km under far gene dispersal conditions. After 100 population bouts of mating and under near gene dispersal conditions, the trial with founder placement producing the greatest population expansion rate exhibited a 314% increase in census size compared with the founder pattern yielding the slowest expansion. Neither loss of alleles nor inbreeding or subdivision was significantly increased under the founder placement patterns yielding the most descendants. Exploring different numerical and geometrical founding scenarios using NEWGARDEN can provide first estimates of founding patterns or stand manipulations that will return the most descendants produced per founder planted in restoration projects.